CONVERSION OF VILLAGE DRUWE RIGHTS BECAME PROPRIETARY RIGHTS ACCORDING TO ARTICLE II PROVISIONS ON THE CONVERSION OF AGRARIAN LAWS (UUPA) - Nonik Latifah (UNISSULA, 2019)
ABSTRACTBali Provincial Regulation Number 3 of 2001 which has been amended by Bali Provincial Regulation number 3 of 2003 concerning Desa Pakraman article 9 paragraph (5) explicitly states that land owned by Pakraman village of Bali cannot be certified in the personal name and Decree of the Minister of Agrarian Affairs and Spatial Planning / Head of National Land Agency Number 276 / Kep-19. 2 / X / 2017 concerning the appointment of Pakraman Village in the province of Bali as the subject of communal ownership rights designates the pakraman village as the subject of joint ownership rights. This brings polemic related to the existence of the village Druwe's land rights. Then the focus of this research is whether the conversion of Druwe Village Rights Into Property Rights According to Article II Provisions for Conversion of the Basic Agrarian Law (UUPA) is in accordance with the law. How should the conversion of Druwe Desa rights to land rights according to the LoGA. as for the research methods used Normative law research (normative law research). The approach used. Statute Approach and Historical Approach. The results of this study are found. Conversion of Village Druwe Rights to Property Rights According to Article II, the Conversion Provisions for the Basic Agrarian Law (UUPA) are not in accordance with the law, because the rights of village druwe with ownership rights do not have in common or similarities either with respect to the subject of the holder of his land rights or the authority of the holder of his right, so that conversions cannot be carried out. This is reinforced by article 9 paragraph (5) of the Regional Regulation of the Province of Bali Number 3 of 2001 which has been amended by the Regional Regulation of the Province of Bali number 3 of 2003 concerning Desa Pakraman regarding land owned by the village of pakraman in Bali cannot be certified in the personal name and the Decree of the Minister of Agrarian Affairs Spatial Planning / Head of National Land Agency Number 276 / Kep-19. 2 / X / 2017 concerning the appointment of Pakraman Village in the province of Bali as the subject of communal ownership rights.